2020
DOI: 10.1002/aoc.5678
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural identification, DNA interaction and biological studies of divalent Mn, Co and Ni chelates of 3‐amino‐5‐mercapto‐1,2,4‐triazole azo ligand

Abstract: New Mn (II), Co (II) and Ni (II) azo chelates of 3-amino-5-mercapto-1,2,4-triazole have been designed and obtained. The structures of these newly isolated complexes were assigned according to elemental, thermal analyses, spectral measurements, conductivity and magnetic moment. The metal complexes were predicted to be not electrolytic from the measured molar conductance values. The magnetic moment and UV-Vis spectral data denoted the formation of octahedral geometries for Mn (II), Co (II) and Ni (II) complexes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…K b of the ligand is the intrinsic binding constant and its value is 1.6 × 10 6 M −1. [ 54,55 ] The observed hyperchromism was due to stacking interactions between the aromatic chromospheres of the complexes and DNA base pairs, which is consistent with the intercalative mode of binding. [ 56,57 ] These observations are similar to those that were reported earlier for various metallo intercalators.…”
Section: Resultssupporting
confidence: 56%
“…K b of the ligand is the intrinsic binding constant and its value is 1.6 × 10 6 M −1. [ 54,55 ] The observed hyperchromism was due to stacking interactions between the aromatic chromospheres of the complexes and DNA base pairs, which is consistent with the intercalative mode of binding. [ 56,57 ] These observations are similar to those that were reported earlier for various metallo intercalators.…”
Section: Resultssupporting
confidence: 56%
“…Gaber et al have reported detailed study on functionalized Schiff bases with various central metal ions like Zn 2+ , Cd 2 , + Co 2+ , Ni, 2+ Cu 2+ , Ni 2+ , Pd 2+ , and Pt 2+ based on spectroscopic modeling studies for antimicrobial, anticancer and DNA binding. [ 11–13 ] On a similar note, acetato, chloro, and nitrato Cu (II) complexes of a novel azo compound, namely, 2,4‐dihydroxy‐5‐[(5‐mercapto‐1 H ‐1,2,4‐triazole‐3‐yl)diazenyl]benzaldehyde, have been reported by Gaber et al [ 14 ] The interaction between the Cu (II) complexes and calf thymus DNA is explored using absorption and viscosity techniques. Among numerous Schiff base(s), Zn (II)‐based functional compounds are rare but pose significant photo physical properties which enable ease in detailed analyses.…”
Section: Introductionmentioning
confidence: 65%
“…It has been reported that the complexation process of biologically active ligands enhances their antitumor activity. Thus, several metal complexes have been prepared and explored for their antitumor activities …”
Section: Resultsmentioning
confidence: 99%